ANALYSIS OF PERSPECTIVES AND PRACTICES OF ZAKAT ON AGRICULTURAL OR PLANTATION PRODUCTS OF THE MUSLIM COMMUNITY OF LAU GUMBA VILLAGE - Rianto, Hartato; Pohan, Syahrial Hasanuddin; Lubis, Sakban (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study aims to find out how the understanding and implementation of zakat, infaq, alms for the Muslim community in Lau Gumba Village. Formulate the advantages and disadvantages of the understanding and implementation of zakat by the community, so that this research can be used as an ingredient in evaluating the community's self by adjusting to Islamic law, and can be a reference for other researchers in research on the development of Islamic philanthropy. Researchers used primary data by conducting research on Muslim communities in Lau Gumba Village with conducting interviews, observations and distributing available questionnaires. The data obtained will be analyzed qualitatively using descriptive analytic. The results of this study indicate that the understanding of Muslim farmers in Lau Gumba Village regarding agricultural zakat is still general, Muslim farmers have not been able to calculate agricultural zakat in accordance with Islamic law. The implementation of the distribution of Islamic philanthropic funds is also done traditionally.